Beyond cabazitaxel: Late line treatments in metastatic castration resistant prostate cancer: A retrospective multicentre analysis. Issue 6 (30th January 2022) - Chazan, Grace; Anton, Angelyn; Wong, Shirley; Shapiro, Julia; Weickhardt, Andrew; Azad, Arun; Kwan, Edmond M; Spain, Lavinia; Gunjur, Ashray; Torres, Javier; Parente, Phillip; Parnis, Francis; et al.
Abstract: Aims: Multiple life‐prolonging therapies are available for metastatic castration‐resistant prostate cancer (mCRPC). However, the optimal treatment strategy following progression through standard treatment with docetaxel, androgen receptor signaling inhibitor (ARSI) and cabazitaxel, remains unclear. We aimed to describe treatment patterns in men with mCRPC following progression on standard treatments and determine whether subsequent treatment choice impacts overall survival. Methods: Clinicopathologic and treatment data were extracted from the electronic CRPC Australian Database (ePAD) for patients who had received docetaxel, ARSIs and cabazitaxel in any order. Data were analyzed to compare groups that did versus did not receive subsequent systemic therapy. Treatment sequences, median duration of treatment, and median overall survival (mOS) were reported for each treatment group. Results: Ninety‐eight eligible patients were identified, with 51 receiving subsequent systemic therapy. Those who received further treatment were younger (68 vs. 71 years, p < .01) but did not have any other differences in clinicopathologic features compared to those who received no further treatment. Patients who received upfront docetaxel were more likely to proceed to subsequent treatment ( p = .02). Subsequent systemic therapies varied, the most common being carboplatin‐based regimens ( n = 13, 25.5%) and many patients were rechallenged with ARSI ( n = 10, 19.6%) or docetaxel ( n = 6, 11.8%). There was no difference in mOS according to subsequent systemic therapy ( p = .09). Conclusion: This retrospective multicenter analysis demonstrates the variation in treatment sequences used for mCRPC in the real‐world setting. In the absence of high quality, prospective evidence, our results suggest that subsequent treatment choice does not influence survival outcomes and the optimal choice is guided by individual patient and disease‐related factors.